Comparative Analysis of Parenting Styles and their Impact on Children's Well-Being: A Cross-Cultural Perspective in Malaysia, China, and Taiwan - Mu, Ye; Pei-Yin, Shih; Chi, Ling Kah; Saeid, Motevalli (International Journal of Child Health and Nutrition, 2024)
Introduction: This research provides an in-depth comparative analysis of parenting styles and their associated communication patterns in Malaysia, Taiwan, and the Chinese mainland. It also explores how they affect children's well-being through social and emotional development. The study examined the evolving parenting styles in four areas: language and verbal communication, non-verbal communication, gender roles and gendered communities, and family communication. Methods: A comprehensive literature search focused on journal articles published between 2018 and 2023. The scientific databases employed for this search encompassed reputable platforms such as Web of Science (WOS), Scopus, PubMed, and Google Scholar. Results: In the language and verbal communication domain, this research offers insights into how parents utilize language as a tool for discipline and emotional expression, indicating a gradual transition in communication styles from authoritarian to democratic. Non-verbal communication sheds light on the nuanced yet impactful ways emotions and norms are conveyed, encompassing eye contact and body gestures. Gender roles and gendered communities unveil a shift in perspectives from traditional to more egalitarian. As these countries or regions progress socially and economically, a transformation in the perception and implementation of gender roles is observed, influencing parenting strategies and children's self-concept. This paper amalgamates these aspects within the realm of family communication to underscore the growing influence of mutual communication and open dialogue in enriching parent-child relationships. Conclusion: The paper concludes that parenting styles are evolving with changing social norms, indicating the adaptability and responsiveness of parents to dynamic social dynamics, ultimately proving advantageous to children's development.